ANALISIS PENGGUNAAN WAKTU LUANG SISWASMP NEGERI 3 PUJUD DILUAR JAM SEKOLAHTAHUN PELAJARAN 2013 / 2014 - ', Yusnita; Arlizon, Raja Arlizon Raja; Umari, Tri Umari Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract ; The title of this project paper is “ The students’ analysis in using spare time outside of school hours at SMP Negeri 3 Pujud in academic year 2013 / 2014 ”. It is descriptive research. In accordance with the symptoms, the writer has some important problems that should be known and overcome. Firstly : “ What are the students’ activities at SMP Negeri 3 Pujud outside of school hours ? ” and secondly : “ What are the factors that influnce the students’ activities at SMP Negeri 3 Pujud outside of school hours ? ”. The objectives of research are : 1. To obtain general description on how the students’ activities at SMP Negeri 3 Pujud outside of school hours and 2. To obtain the factors that influnce the students’ activities at SMP Negeri 3 Pujud outside of school hours. The research was conducted at SMP Negeri 3 Pujud. Then, The subject of the research is the students of SMP Negeri 3 Pujud and the object of this research is the students’ activities in using spare time outside of school hours. In order to collect the data of this research, writer uses questionnaire and it contains thirty items. After obtain the data, the weriter computes by using the following formula :P = x 100 %.In obtaining the students’ activities in using spare time outside of school hours, writer uses the following criteria :10 – 14 is high, 5 – 9 is middle, and 0 – 4 is low.Finally, based on the writer’s investigation, the students’ activities in using spare time outside of school hours is categorized middle. It means that most of the students of SMP Negeri 3 Pujud use their spare time outside of school hours by doing useful activities. The last, one of the factors that influence the students’ activities in using spare time outside of school hours is the internal factor, namely : the students do not have high self motivation to do the positive things as a student. Key words : Spare time, Student, and School hours